TANGGUNG JAWAB HUKUM NOTARIS REKANAN PERBANKAN YANG TIDAK MENYELESAIKAN AKTA YANG TELAH DIBUATNYA - Dinda Anwar (Ilmu Hukum Prima (IHP), 2021)
A Notarial deed can become a legal ground for a person’s status of property, right and obligation. Errors in making it can cause the revocation of his right and obligation or his burden and obligation. A Notary has the authority to make an authentic deed on any action, contract, and provision specified by law and intended by the persons appearing in authentic deeds, to guarantee the date it is made, to keep the deeds, to give Grosse, and the copies and the excerpts, as long as they are not assigned or exempted to officials. The objective of the research was analyze the liability of a Notary for the deeds he had made, to analyze the legal consequence of a Notary as a banking partner who neglected his deeds, and to find out legal protection for the Bank wich deeds were neglected by the Notary as the Bank partner.